The Influence of Teacher Performance, Competence, and Motivation in Improving the Quality of Education in Islamic Educational Institutions: An Analysis with the Smart PLS Method - Ramdhan, Tri wahyudi; Abdurakhmonovich, Yuldashev Azim; Yusuf, Achmad (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
This study aims to explore the influence of competence, work motivation, and managerial strategies on teacher performance and their impact on the quality of education in Islamic educational institutions. The focus of the research is directed at integrated Islamic madrassas and schools, which are committed to maintaining the quality of education amid limited resources. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) method was used to analyze the causal relationship between these variables, with data obtained through surveys from teachers in several Islamic educational institutions. The results of the study show that teacher competence has a significant effect on teaching performance, which ultimately improves the quality of education. In addition, work motivation plays an important mediating role, where continuous career development can maintain teacher commitment. Managerial strategies implemented by school leaders also contribute positively to increasing productivity and teacher focus in teaching. This study concludes that the combination of competence, motivation, and adequate managerial support is a key factor in improving teacher performance and education quality in Islamic educational institutions. This finding provides recommendations for managers of Islamic educational institutions to focus on developing human resources to achieve optimal quality of education